South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Conceituando Empoderamento na Perspectiva Feminista - Sardenberg, Cecília M B (2006)
Transcription d’une communication au séminaire International : « Trilhas do empoderamento de mulheres », Salvador da Bahia, 5-10 juin 2006.
Keywords: amérique latine; amériques; anthropologie; approches et analyses; brésil; cours; cycles supérieurs; discipline; empowerment; fem7000; inégalités; justice sociale; militance; mouvements sociaux; patriarcat; pratiques féministes; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sofia; systèmes d'oppressions; thématiques; épistémologie